2002
DOI: 10.1016/s0167-4889(02)00196-9
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Src-dependent Raf–MEK1/2–ERK signaling pathway is required for IL-1α-induced upregulation of β-defensin 2 in human middle ear epithelial cells

Abstract: beta-defensin 2 is produced by a variety of epithelial cell types in the body and exhibits potent antimicrobial activity against a variety of pathogens, including the bacteria that are most commonly associated with otitis media (OM). The human beta-defensin 2 (hBD-2) gene is an NF-kappa B regulated gene and a variety of proinflammatory stimuli can induce its expression. Although the presence of molecules of innate immunity such as lysozyme and lactoferrin has been demonstrated in the middle ear, to date there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
74
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 58 publications
7
74
0
1
Order By: Relevance
“…IL-1α activates the ERK signaling pathway, which is known to be important for HBD2 expression [17]. The present study confirmed the effect of IL-1α on the activation of the ERK signaling pathway, and in addition, we found that Ile treatment extended the interval of the activation of the ERK signaling pathway.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…IL-1α activates the ERK signaling pathway, which is known to be important for HBD2 expression [17]. The present study confirmed the effect of IL-1α on the activation of the ERK signaling pathway, and in addition, we found that Ile treatment extended the interval of the activation of the ERK signaling pathway.…”
Section: Discussionsupporting
confidence: 88%
“…GPCRs comprise a large protein family of transmembrane receptors that sense molecules outside the cell [31]. Once a ligand binds to a GPCR, the structure of the GPCR is changed, and a trimer-forming G protein is activated, leading to changes in the concentration of second messengers such as calcium ions and cAMP, and the subsequent activation of internal signal transduction pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hBD-1 is constitutively expressed in normal and inflamed nasal and middle ear mucosae, whereas hBD-2 is expressed only in inflamed tissues (8,9). Additionally, inducible hBD-2 expression was demonstrated in both a human middle ear epithelial cell line and in primary nasal epithelial cells in response to proinflammatory cytokines or bacterial components, a common feature of hBD-2 expression in multiple in vitro systems (10). The detection of these defensins in nasal and middle ear mucosae suggests a role for these peptides in maintaining the health of the uppermost airway and thus perhaps preventing OM.…”
mentioning
confidence: 94%
“…Beta defensin 2, which is released from the epithelial cells in response to microorganisms or cytokines, exhibits potent antimicrobial activity against gramnegative bacteria and candida. HMEEC-1 cells were found to up-regulate beta defensin 2 in response to interleukin 1 alpha (IL-1a) via a Srcdependent Raf-MEK1/2-ERK signaling pathway [34]. We also found that nontypeable H. influenzae-induced up-regulation of beta defensin 2 requires a TLR2/MyD88-dependent p38 MAP kinase pathway [35].…”
Section: Induction Of Antimicrobial Agentsmentioning
confidence: 87%